Squamous Cell Carcinoma of the Tongue with Metastasis to Myocardium: Report of a Case and Literature Review. (17th October 2019) - Shafiq, Ali; Samad, Fatima; Roberts, Eric; Levin, Jonathan; Nawaz, Ubaid; Tajik, A. Jamil
Abstract : This is a case of a 43-year-old man who in 2014 was diagnosed with oral squamous cell carcinoma involving the tongue. He underwent extensive surgery that involved right tongue cancer resection and reconstruction with a free flap graft from his right forearm. He then was started on chemotherapy and radiation. Surveillance computed tomography in December 2016 showed a cardiac lesion in the left ventricular apex, which was confirmed by further echocardiography and cardiac magnetic resonance imaging. A biopsy of the mass revealed metastatic squamous cell carcinoma. He was deemed to not be a surgical candidate and continued on palliative chemotherapy. The patient had a very poor prognosis and eventually succumbed to the disease, highlighting the importance of surveillance imaging in such cases. A high index of suspicion on the part of the physician is needed to help in the early identification of these patients.